PENENTUAN KADAR FENOLIK TOTAL EKSTRAK ETANOL 96% DAUN TERAP (Artocarpus odoratissimus Blanco) DENGAN METODE SPEKTROFOTOMETRI VISIBEL - Anna Khumaira Sari; Noor Aisyah; Erna Prihandiwati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Terap leaf (Artocarpus odoratissimus Blanco) is a plant that contains flavonoids which are phenolic groups. These compounds are effectively used as natural antioxidants. Antioxidants function to reduce the speed of lipid peroxidation by giving electrons to free radicals, can make normal molecules. Phenol compounds also have bacteriosid, antihelmintic, analgesic, anti-inflammatory, antimicrobial, anticancer and degenerative diseases. The purpose of this study was to determine the total phenolic levels contained in the terap leaf plants. The terap leaves were obtained from Amuntai City, Hulu Sungai Tengah which were selected based on inclusion and exclusion criteria. Phenolic compounds in terap leaves were extracted using maceration method using 96% ethanol solvent. Qualitative testing of terap leaf was determined using FeCl3 reagent, determination of terap leaf compounds was expressed with gallic acid equivalence value. The method used is Visible Spectrophotometry with Folin ciocalteau reagents. The concentrations used in linear regression curves are 5, 10, 15, 20, 25 and 30µg / mL. Qualitative test results obtained the terap leaf extract positive containing phenolic compounds with marked changes in yellow to green. Based on quantitative test results obtained operating time at minute 1 and the maximum wavelength obtained is 762 nm. Linear regression obtained by y = 0.0213x + 0.117. The value of total phenolic content obtained in the terap leaf extract was 10.56% w / w.